2007
DOI: 10.1128/jvi.00247-07
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus Caspase Inhibitors P49 and P35 Block Virus-Induced Apoptosis Downstream of Effector Caspase DrICE Activation in Drosophila melanogaster Cells

Abstract: Baculoviruses induce widespread apoptosis in invertebrates. To better understand the pathways by which these DNA viruses trigger apoptosis, we have used a combination of RNA silencing and overexpression of viral and host apoptotic regulators to identify cell death components in the model system of Drosophila melanogaster. Here we report that the principal effector caspase DrICE is required for baculovirus-induced apoptosis of Drosophila DL-1 cells as demonstrated by RNA silencing. proDrICE was proteolytically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 58 publications
1
85
0
Order By: Relevance
“…Similarly, in discs expressing the anti-apoptotic baculovirus protein p35, which inhibits the effector caspases Drice and DCP-1 (Xue and Horvitz 1995; Kondo et al 2006;Xu et al 2006;Baum et al 2007;Lannan et al 2007), no acridine orange staining was observed at any time point ( Figure S2E). Because p35 inhibits effector caspase activity after proteolytic cleavage, cleaved caspase-3 staining can still be observed once these caspases are activated ( Yuet al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in discs expressing the anti-apoptotic baculovirus protein p35, which inhibits the effector caspases Drice and DCP-1 (Xue and Horvitz 1995; Kondo et al 2006;Xu et al 2006;Baum et al 2007;Lannan et al 2007), no acridine orange staining was observed at any time point ( Figure S2E). Because p35 inhibits effector caspase activity after proteolytic cleavage, cleaved caspase-3 staining can still be observed once these caspases are activated ( Yuet al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The generation of dsRNA and transfection methods were performed as previously described (30). Cells were transfected with ago2-specific dsRNA in suspension and maintained in monolayer for 1 day at 27°C prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of these perturbations fell into two classes. All anti-apoptotic genotypes showed a complete [bantam overexpression, known to downregulate Drosophila hid (Brennecke et al, 2003) and expression of p35, a baculoviral inhibitor of effector caspases (Lannan et al, 2007)] or nearly complete (DIAP1 overexpression) suppression of delamination and delayed closure, evident from the absence of rosettes. Pro-apoptotic perturbations (overexpression of hid or reaper) significantly increased the number of delaminations and hastened closure ( Fig.…”
Section: An Apoptotic Signal Provides Necessary and Sufficient Autonmentioning
confidence: 99%